The effectiveness of Personal Selling on company performance. A case of C.T. Bolts - Chiwerera, Dareen Anesu (Midlands State University, 2020)
The research conducted was to investigate the effectiveness of personal selling on company performance of Zimplow Holdings ltd t/a C.T. Bolts. The company was facing a diminishing trend in its sales and hence management took a decision to refocus its efforts on personal selling so as to improve the firm’s performance. Objectives of the study were to explore the effects of sales presentation on market share, to examine the effects of sales presentations on sales volume and to establish the effects of handling objections on customer loyalty The study was conducted in Bulawayo on C.T. Bolts customers, employees and management. After adopting a sample size of 55 respondents, the researcher administered questionnaires and face to face interviews to the respective parties. The results of this study were presented using pie charts and bar graphs after the analysis of the data was done through SPSS and interpreted using mean and percentages. Findings in the study, were gathered and supported by primary and secondary data. The researcher obtained this data during the course of the research. Findings showed that prospecting has a positive effect on market share of the company. The research also uncovered that, sales presentations effective on increasing sales volume of the company, where sales persons adapt their presentation in order to convince customers to make a purchase. Lastly, handling objections results in customer loyalty because it involves communication and assistance to the customer, which provides a great sense of service quality. Therefore, the researcher recommended that C.T. Bolts may adopt training salespersons on adapting their presentations so as to conform to different selling situations. More so, management may also consider investing more time in prospecting as it increases the customer base. Lastly, the researcher suggested that salespersons address consumer queries quickly so as to maintain a positive perception on service quality.